2018
DOI: 10.5603/nmr.a2018.0012
|View full text |Cite
|
Sign up to set email alerts
|

Significance of splenic uptake on somatostatin receptor imaging studies

Abstract: Spleen shows a high physiological uptake on radionuclide somatostatin receptor (SSTR) imaging studies. Autoradiography and immunohistochemistry studies showed that SSTRs are mainly located in the red pulp of the spleen. In this review article we will summarize the significance of splenic uptake in SSTR imaging studies and will also present high resolution splenic images of Ga-68 DOTANOC PET in which splenic distribution of the radiotracer appears to be correlating with the distribution of red pulp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…This is an important diagnostic pitfall, which led to unnecessary surgery in our patient. The splenic uptake of radionuclide somatostatin seems to be mainly caused by the presence of somatostatin receptors located in the red pulp of the spleen, mainly SSTR2 (79,7%) [16]. The presence of SSTR2A in the accessory splenic tissue in our case was confirmed by additional immunohistochemical staining by our pathologist, as is shown in image 4…”
Section: Nuclear Imagingsupporting
confidence: 69%
“…This is an important diagnostic pitfall, which led to unnecessary surgery in our patient. The splenic uptake of radionuclide somatostatin seems to be mainly caused by the presence of somatostatin receptors located in the red pulp of the spleen, mainly SSTR2 (79,7%) [16]. The presence of SSTR2A in the accessory splenic tissue in our case was confirmed by additional immunohistochemical staining by our pathologist, as is shown in image 4…”
Section: Nuclear Imagingsupporting
confidence: 69%
“…A further interesting observation from our study was the there was generally a higher SUVmax in reference tissues (normal liver and spleen) at iPET in patients who responded to PRRT. In the normal liver SSTRs are predominantly found in bile ducts, whereas in the normal spleen, autoradiography and immunohistochemistry studies have shown that they are found predominantly in red pulp (21,22). This reason for the presumed flare phenomenon in tracer uptake in normal tissues with high expression of SSTR is uncertain; however, it may reflect an inflammatory response with increase in activated macrophages that overexpress SSTR-1 and 2 on their cell surface (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…CT and MRI show attenuation and enhancement of the accessory spleen similar to the spleen in all phases. In contrast, pancreatic tumors show greater attenuation in the arterial phase and less in the venous phase on CT. On MRI, splenic tissue in the pancreatic tail often shows low signal intensity in T1 and high intensity in T2 when compared to pancreatic parenchyma; moreover, intratumoral hemorrhage and necrosis are absent in splenic tissue and may be seen with neoplasms [ 20 ]. In difficult cases, Technetium Tc 99m sulfur colloid scintigraphy can be utilized in differentiating splenic tissue from pancreatic tumors.…”
Section: Discussionmentioning
confidence: 99%